Engineering documentation control handbook configuration management in industry. - Watts, Frank B. (W. Andrew, 2008)
Control of engineering documentation, sometimes called Configuration Management (CM) especially in the defense industries, remains critical to world-class manufacturing survival. The 3rd edition of this popular engineering documentation handbook improves upon one of the best blueprints for efficient EDC/CM ever published, and continues to provide a significant company strategy for managers, project leaders, chief engineers and others. It can be used in many industries to improve the control of engineering documentation.
Keywords: Engineering -- Management.; Engineering -- Documentation.; Configuration management.; Production management.; elektronické knihy; electronic books